The Effect of Ownership Structure and Company Transparency on Tax Avoidance with Profitability as Moderating Variables - Vicky Firmando; Erna Setiany (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to examine the moderating role of institutional ownership and corporate transparency on tax avoidance and profitability among manufacturing firms traded on the Indonesia Stock Exchange throughout the period 2018-2020. The quantitative approach was taken in the planning of this study. Purposive sampling was utilized to collect data from as many as 64 businesses per year. During the study's three-year observation period, 192 participants were served as the overall sample size. As shown by the data, institutional ownership and corporate openness are factors that reduce tax avoidance. Then, Profitability moderates the institutional ownership of Tax Avoidance, but it does not moderate the corporate transparency that results from Tax Avoidance.